Learn Windows PowerShell in a Month of Lunches, Third Edition, Video Edition - Jones, Don; Hicks, Jeffery (Manning Publications, 2019)
"Superb ... full of real-world examples, this book is an IT specialist's best friend." Olivier Deveault, Voxco Group Learn Windows PowerShell in a Month of Lunches, Third Edition is an innovative tutorial designed for busy IT professionals. This updated edition covers PowerShell features that run on Windows 7, Windows Server 2008 R2 and later, PowerShell v3 and later, and includes v5 features like PowerShellGet. PowerShell is both a scripting language and an administrative shell that lets you control and automate nearly every aspect of Windows. It accepts and executes commands interactively and you can write scripts to manage most Windows servers like Exchange, IIS, and SharePoint, as well as online services like Azure and Office 365. Learn Windows PowerShell in a Month of Lunches, Third Edition is an innovative tutorial designed for busy IT professionals. Just set aside one hour a day - lunchtime would be perfect - for a month, and you'll be automating Windows tasks faster than you ever thought possible. This updated edition covers PowerShell features that run on Windows 7, Windows Server 2008 R2 and later, PowerShell v3 and later, and includes v5 features like PowerShellGet. Inside: Learn PowerShell from the beginning, no experience required! Covers PowerShell v3 and up, Windows 7, and Windows Server 2008 R2 and later Each lesson takes you an hour or less Experience with Windows administration is helpful. No programming or scripting experience needed. Veteran PowerShell MVPs Don Jones and Jeffery Hicks bring years as successful trainers to this concise, easy-to-follow book/course. Your key to learning Windows PowerShell. Noreen Dertinger, Dertinger Informatics A must-have ... both novice and expert will benefit from this book. Tiklu Ganguly, Mazik Global Learn PowerShell fundamentals from the experts. James Berkenbile, Berkenbile Consulting NARRATED BY LOU FERNANDEZ
Online resource; Title from title screen (viewed February 27, 2019)
Keywords: Internet videos; Streaming video; Vidéos sur Internet; Vidéo en continu; streaming video; Electronic videos